Folha diagnótica para avaliação do estado nutricional do feijoeiro - de Souza, Henrique A.; Hernandes, Amanda [UNESP]; Romualdo, Liliane M.; Rozane, Danilo E. [UNESP]; Natale, William [UNESP]; Barbosa, Jose C. [UNESP] (Universidade Federal da Paraíba (UFPB) Ccsa, 2011)
The bean is a nutrient demanding plant, either due to the small and shallow root system or due to the short cycle. A study with doses of lime and boron was conducted and correlations were made between two types of leaf (+ 1 and + 3) of the bean with the contents of these elements in plants and production, aiming to establish the most appropriate leaf for diagnosis of nutritional status. The experiment was conducted in greenhouse conditions employing bean seeds cv. BRS Talisma. Lime rates considering the saturation of bases (70%), were calculated as zero, half the standard dose, dose to increase V = 70% (default), one and a half and twice the standard dose, while the boron amounts used were: zero, 0.6, 1.2, 1.8 and 2.4 mg B dm(-3). At the time of flowering, diagnostic leaves + 1 and + 3 (mature leaves from the apex) were collected along with sampling of a plant (aerial part) per pot and the measurement of production. Through correlations it was verified that nutrients, calcium, magnesium and boron in the leaf + 3 showed higher correlation coefficients with levels in the plant and production data.
Diagnostic leaf for evaluation of the nutritional status of bean
Keywords: Phaseolus vulgaris; liming; boron